Identification of gaharu tree (Aqualaria malacensis) and gaharu oil distillation process as the local content included in 21st century curriculum on the subject of high level botany - Herliani; Ibrahim, M; Rahayu, Y S (IOP conference series. Earth and environmental science, 2019)
Gaharu tree (Aquilaria malaccensis) is the most potential type of gaharu tree. Based on the subject of high level botany as included in the 21st century curriculum, students are encouraged to observe any local wisdom, including the identification of gaharu tree. The purposes of this study are to recognize students' concept mastery of gaharu tree identification and students' performance of gaharu oil distillation process. The data were analyzed quantitatively. Forty students of Biology study program who are taking high level botany subject participated in this study. They were divided into two classes: twenty one students of class A and nineteen students of class B. The result showed that the concept mastery of gaharu tree identification for both classes were good. Class A obtained 85.71, while class B was 94.74. For distillation process activity, the mean score for class A was 87.3 and class B was 88.9. Based on the results, it can be concluded that students' mastery concept of gaharu tree (Aqualaria malacensis) identification and students' performance of gaharu oil distillation process have good criteria. These could be used as the learning activities in the local content included in 21st century curriculum on the subject of high level botany.